Parallel multiple watermarking using adaptive Inter-Block correlation. (1st March 2023) - Wang, Xingrun; Yuan, Xiaochen; Li, Mianjie; Sun, Ying; Tian, Jinyu; Guo, Hongfei; Li, Jianqing
Highlights: Embedding multiple watermarks method based on inter-block correlation is proposed. The texture complexity method is designed to adaptively select adjacent blocks. Multiple watermarks are embedding in the same region of the image in parallel. Two methods of adjacent block selection are proposed for image adaptive selection. The watermark is embedded alternately in the middle frequency and low frequency. Abstract: People pay more and more attention to copyright protection and digital watermarking technology is a reliable method for copyright identification. In this paper, we propose the parallel multiple watermarking method using adaptive inter-block correlation. Considering the image texture characteristics, the texture complexity method is designed, based on which, the Circular-shaped Adjacent Block Selection and the Arch-shaped Adjacent Block Selection will be adaptively selected for adjacent block selection. The multiple watermarks are alternately embedded into the low and middle frequency band in DCT domain of the image blocks to good imperceptibility and high robustness. By adjusting the difference of projection of embedding coefficients and reference coefficients on the spreading vector, the multiple watermarks can be embedded, so the embedding capacity increases. In addition, we improve the multiple watermarks embedding based on orthogonal spreading vectors so that it can be adapted to embedding multiple watermarks in parallel based on inter-block correlation, saving embedding and extraction time. We theoretically analyze the rationality of parallel orthogonal embedding of multiple watermarks and experimentally verify the high efficiency of parallelism. Cover images of different texture complexity are included in the test dataset, and various attacks have been simulated in the experiments. Experimental results on imperceptibility, robustness, time cost and watermark capacity show the satisfied performance of the proposed scheme.